Regional economic integration and the backward integration of ECOWAS sub-region into global value chains. (9th August 2019) - Obasaju, Barnabas Olusegun; Olayiwola, Wumi Kolawole; Okodua, Henry; Adekunle, Babatunde Sunday
This paper examines the impact the economic community of West African States (ECOWAS) as a regional economic community (REC) has exerted on the backward integration of her member states into global value chains between 2007 and 2012. The conventional indicator of regional economic integration is compared vis-á-vis a relatively newly proposed indicator in order to investigate which one performs better in respect of economic expectations. Using the systems generalised method of moments, this study finds that the newly proposed indicator, which uses the rest of the world as the benchmark rather than the world while measuring the indicator of regional economic integration, outperforms its counterpart. Estimates also show that although ECOWAS as a REC has contributed positively to her members' backward integration into GVCs, this contribution is not statistically significant. To enhance members' access to the needed quality inputs via the backward integration, more intensified efforts are needed from this REC.